How do presentation age and CSF opening pressure level affect long-term prognosis of pseudotumor cerebri syndrome in children? Experience of a single tertiary clinic - DAĞÇINAR, ADNAN; ASLAN, BÜLENT; TÜRKDOĞAN, DİLŞAD; ÜNVER, OLCAY; DERİCİOĞLU, VOLKAN (Springer Science and Business Media Deutschland GmbH, 2021)
Background: Diagnosis and treatment of pseudotumor cerebri syndrome in children is still a challenge for clinicians. The aim of this study is to reveal the influence of presentation age and CSF opening pressure on long-term prognosis of pseudotumor cerebri and share our clinical data of the very young age (≤ 5-year) group. Method: This retrospective study includes the patients followed by the Marmara University Pediatric Neurology Clinic between years 2012 and 2020 diagnosed with definite, probable, or suggestive pseudotumor cerebri syndrome according to modified Friedman criteria. Patients were classified into three groups according to presentation age: group 1: ≤ 5 years old; group 2: 6–10 years; and group 3 > 10 years old. CSF opening pressure was also categorized into three groups as CSF < 20 cmH20; CSF 20–30 cmH20; and CSF > 30 cmH20. Results: One hundred three patients, 62.1% female (n = 64), were enrolled in the study. Group 1 consisted of 16 patients (60% male), group 2 consisted of 30 patients (63.3% female), and group 3 consisted of 57 patients (66.7% female). The mean CSF opening pressure did not differ between the three age groups in our study (p > 0.05). Treatment response was not correlated with CSF opening pressure. Papilledema presence and level of CSF opening pressure were independent of age (p > 0.05). Conclusions: Age at presentation and CSF opening pressure at diagnosis are not any predictive factors that influence long-term prognosis of pseudotumor cerebri syndrome in children. Evaluation and follow-up of children should be done in personalized approach. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Age; And correlation of our findings is done compared to the literature; Children; CSF pressure; Papilledema; Pseudotumor cerebri